Mortality Reporting and Rumor Generation: An Assessment of Crisis and Emergency Risk Communication Following Hurricane Maria in Puerto Rico (Journal of International Crisis and Risk Communication Research, 2020)
This study assessed the Government of Puerto Rico’s crisis and emergency risk communications following Hurricane Maria and the post-disaster information environment to identify factors that may have contributed to negative public perceptions of mortality reports. Data included Government of Puerto Rico press releases, press conference audio recordings and Facebook Live transmissions, digital media news and social media commentary, and interviews with Government of Puerto Rico personnel and community stakeholders. Study findings indicate that inadequate crisis communication planning and training, coupled with information gaps and inconsistencies, contributed to rumors around the issue of mortality. As a consequence, the Government of Puerto Rico lost the ability to effectively manage messaging, thus decreasing their credibility, perceived transparency, and public trust. Recommendations regarding future preparedness activities and research are offered.